PROFIL LITERASI SAINS DAN KETERAMPILAN BERPIKIR KRITIS PENDIDIK IPA SMP - Jamaluddin Jamaluddin; A. Wahab Jufri; Agus Ramdani; Afriana Azizah (Postgraduate, University of Mataram, 2019)
Secondary school science educators need to have good scientific literacy and critical thinking skills, so that they have sufficient competency to teach students to be able to compete in the current and future information and globalization. The purpose of this research was to determine the profile of scientific literacy and critical thinking skills of science educators. The subjects of this study were secondary school science educators who were still actively carrying out their professional duties. This study uses descriptive research methods. The instrument of data collection consists of scientific literacy instruments and instruments of critical thinking skills. The results of the study show that the science literacy profile of science educators is on average categorized as sufficient. The profile of the science literacy skills of junior high school educators is categorized as 33.33% in the good group, 16.67% in the sufficient category, and 50% in the less category. Profile of the average critical thinking skills of science educators in the medium category. Science educators who have high critical thinking skills are 32%, those with moderate critical thinking skills are 32%, and those who have low critical thinking skills are 36%.Keywords: Literacy Science, Critical Thinking, Science Educators.